ANALISIS HUKUM ISLAM TERHADAP PEMBATALAN SEPIHAK OLEH KONSUMEN GRABBIKE Di PT. GRAB CABANG PURWOREJO - Muhajir; Akhmad Syaikhu; Septian Fiktor Riyantoro (At Tasyri'i : Jurnal Program Studi Perbankan Syariah, 2021)
Grabbike orders can be made via a smartphone application which can bedownloaded on the Play Store site. However, in practice there are passengerswho cancel their bookings unilaterally, resulting in losses to the driver. Startingfrom the above problems, the researchers focused their research on theformulation of the problem: First, how is the Islamic law review of the onlinegrabbike transportation service contract mechanism in Purworejo. Second, how isthe review of Islamic law on the application of online grabike transportation ratesin Purworejo. This type of research used by the author is field research (fieldresearch) with a qualitative approach method. The data collection technique isdone by interview, observation and documentation. The data analysis used isdeductive data analysis (from general-specific). The result of this research is thatthe contract mechanism implemented by online grabbike transportation servicesis in accordance with Islamic law. While unilateral cancellation by grabbikeconsumers to drivers is allowed